Factors Associated with Public Transportation Drivers’ Compliance with Smoke-Free Area Regulations at Depok City Terminal - Ihyani Nurdiena Marliamara; Tri Krianto; yaya, Dien Anshari; yaya, Faika Rachmawati; yaya, Puji Lestari (RADJA PUBLIKA, 2026)
Smoking remains one of the most significant public health challenges in Indonesia, with serious impacts on mortality rates, economic burden, and low compliance with Smoke-Free Area policies. This study aimed to analyze factors associated with public transportation drivers’ compliance with Smoke-Free Area (SFA) regulations at the Depok City Terminal in 2024. This study employed a descriptive method with a quantitative approach and a cross-sectional design. The respondents consisted of 94 public transportation drivers selected using purposive sampling. Data were collected through a structured questionnaire covering individual characteristics as well as smoking attitudes and behaviors. Data analysis was conducted using the Chi-square test. The results showed that the majority of public transportation drivers (79.8%) were non-compliant with SFA regulations, while only 20.2% were compliant. Predisposing factors were significantly associated with drivers’ compliance (p-value < 0.05), as were enabling factors. However, the reinforcing factor, namely cigarette price, was not significantly associated with compliance. Keywords: Compliance, Public Transportation Drivers, Smoke-Free Areas